O enfoque CTS no ensino de matemática: as contribuições de um curso de formação de professores - Amorim, José Carlos (2023)
Mathematics teaching has faced many difficulties, obtaining results far below expectations, and the curricular component that is explicitly related to everyday life has been considered the terror of most students. It is clear that teachers need to seek methodologies capable of making Mathematics teaching meaningful and attractive to students. In this sense, it is believed that when the proposed contents are worked in a contextualized way, avoiding fragmentation, it awakens the interest of students, motivating them to interact, and thus achieve learning. In this purpose, of relating Mathematics teaching to the student's experience in society, Mathematics teaching with a Science-Technology-Society (STS) focus is constituted as a methodology. In view of the above, this research was guided by the following question: What is the relevance of a training course for Mathematics teachers that takes the STS approach as a contextualizing support in order to contribute to the pedagogical practices of those involved? In order to address this question, the general objective is to develop teaching material for Mathematics teachers, structured on the premises of the CTS approach. In the current state of education, highlighting the teaching of Mathematics in basic education, it is evident that there is a need for discussions that seek methodologies that make sense and relate what is taught to the reality of the student's life, thus promoting meaningful and motivating learning, since we still come across many teachers who are unprepared to make classes more attractive by explaining why and for what purpose mathematical concepts should be learned. The educational product linked to this dissertation is a teaching material aimed at Mathematics teachers in basic education, and is presented as a compilation of activities with a focus on STS in the grafting modality, originating from other educational products. The implementation of the proposal took place through a training course for twenty-five Mathematics teachers in basic education, which took place at the Carlos Gomes School, located in the city of Cacoal, State of Rondônia. The course had a 12-hour workload and was developed in three face-to-face meetings. To analyze the feasibility of the proposal and the possible contributions of the CTS approach to teaching Mathematics, a qualitative and participatory research was conducted, and data were collected through three instruments: a questionnaire (initial and final), teaching sequences produced by teachers during the course, and the research teacher's logbook. Data analysis indicated positive results, since the activities carried out, based on the educational product, were well accepted by teachers and they indicated an interest in using the teaching material in their classes. The teaching sequences produced by teachers during the course presented the CTS approach permeating the structure. It was observed that participants understood that teaching Mathematics with the CTS approach is capable of meeting the demands and thus meeting the requirements of the National Common Curricular Base, classifying the methodology as innovative in terms of teaching Mathematics. The educational product is free and open access and is available for download on the EduCapes portal at.